Sources of Methane Emissions (Vista-CA), State of California, USA - Hopkins, F.M.; Rafiq, T.; Duren, R.M. (ORNL Distributed Active Archive Center, 2019)
This dataset provides spatial data products with identified and classified locations of potential methane (CH4) emitting facilities and infrastructure spanning the State of California. These data products form a GIS-based mapping database designed to address shortcomings in current CH4 source inventories and is known as Vista California (Vista-CA). Vista-CA consists of detailed spatial maps for facilities and infrastructure in the State that are known or expected sources of CH4 emissions and illustrates the spatial distribution of potential CH4 sources. Vista-CA spatial data sets were created utilizing an assortment of publicly available data sources from local, state, and federal agencies for the years 2005 to 2019. The final Vista-CA database contains over 230,000 entries, which are presented as fifteen CH4 emitting infrastructure maps. The database was used to support flight planning and source attribution for the California Methane Survey project.
North American Carbon Program (NACP)
Keywords: ATMOSPHERE > AIR QUALITY > EMISSIONS; HUMAN DIMENSIONS > HUMAN SETTLEMENTS > URBAN AREAS; HUMAN DIMENSIONS > INFRASTRUCTURE; ATMOSPHERE > ATMOSPHERIC CHEMISTRY > CARBON AND HYDROCARBON COMPOUNDS > METHANE; Environmental Modeling > Computer; facilities and infrastructure; IPCC sector; CH4 Sectors; CH4 Source; methane emissions; Vista-LA